Analisis Perbandingan Tagline "Jagonya Ayam" pada Iklan KFC dengan Tagline "We Got You" pada Iklan Wendy's terhadap Brand Awareness Produk bagi Pengguna Media Sosial X - Malau, Paskal Zefanya; Salsabila, Talitha Aryana; Efendi, Fairuz Irhab Adinata; Azizah, Anisa Nur; Ferdinand, Cleo Firman; Alghifari, Ahmad Rifki; Maharani, Neysa Defi; Sholihatin, Endang (Innovative: Journal Of Social Science Research, 2025)
In marketing a product, it is necessary to have a promotion so that the product or business name can be known among the public. One of the marketing strategies that can be done is to use a tagline. Tagline is a short sentence made by a company to convey the core message of a product, service, or brand in a unique, interesting, and memorable way. Tagline is used to influence the audience by building Brand Awareness and strengthening brand identity. Big companies such as KFC with the tagline "Jagonya Ayam" and Wendy's with the tagline "We Got You" have succeeded in creating a strong identity through short sentences. The purpose of this research is to 1) Find out the impact of using taglines in KFC and Wendy's ads on the level of product Brand Awareness, 2) Find out the right characteristics of KFC and Wendy's taglines in increasAdd Contributoring Brand Awareness on platform X, 3) Find out whether the frequency of KFC tagline ads can increase Brand Awareness according to X platform users. Research using qualitative methods through indirect interviews using google forms that are distributed through social media X. The research results show that 1) The use of the tagline "Jagonya Ayam" on KFC ads and "We Got You" on Wendy's ads has an impact on the level of product brand awareness. 2) KFC tagline is more effective than Wendy's because it has the characteristics of shorter sentences, easy to remember, and more relevant to the main product sold, namely chicken. 3) The frequency of advertising impressions plays an important role in increasing product brand awareness. The more often an advertisement is shown, the stronger its influence on consumer memory and brand recognition. Therefore, the use of the right tagline and effective advertising strategy can significantly increase brand awareness.